2022
DOI: 10.3389/fimmu.2022.1057839
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide DNA methylation of Munro’s microabscess reveals the epigenetic regulation in the pathogenesis of psoriasis

Abstract: IntroductionMunro's microabscess is a typical pathological feature in the early psoriatic lesion, mainly characterized by the accumulation of neutrophils in the epidermis. DNA methylation microenvironment of Munro's microabscess and the crosstalk with transcription and its effect on neutrophils have not yet been revealed.MethodsPerformed genome-wide DNA methylation analysis and further differential methylation analysis of psoriatic skin lesions with and without Munro's microabscess from two batch samples consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…In addition, it has been found that there is a certain correlation between differentially methylated genes and typical histopathological abnormalities of psoriasis (e.g., Munro microabscesses, parakeratosis, and neutrophil infiltration). [322][323][324] However, most of the current studies on DNA methylation in psoriasis used skin tissue or peripheral blood as samples, and cellular heterogeneity might have interfered with the actual influence of epigenetics on psoriasis.…”
Section: Epigenetic Regulationmentioning
confidence: 99%
“…In addition, it has been found that there is a certain correlation between differentially methylated genes and typical histopathological abnormalities of psoriasis (e.g., Munro microabscesses, parakeratosis, and neutrophil infiltration). [322][323][324] However, most of the current studies on DNA methylation in psoriasis used skin tissue or peripheral blood as samples, and cellular heterogeneity might have interfered with the actual influence of epigenetics on psoriasis.…”
Section: Epigenetic Regulationmentioning
confidence: 99%
“…DNA hypermethylation likely mediates the binding of proteins from the AP-1 family (FOS, FOSB, and JUND), influencing signaling pathways and playing a role in the formation of psoriatic Munro's microabscess [62].…”
Section: Dna Methylationmentioning
confidence: 99%